2019
DOI: 10.1017/s1479262118000539
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic analysis of water deficit tolerance in coriander through physiological traits

Abstract: Drought stress restricts the production of agricultural crops through morphological, physiological and biochemical changes in plants. This study explored the genetic control of physiological traits related to drought in coriander. In a diallel analysis, all six parents, their 15 F1 hybrids and 15 F2 populations were subjected to different irrigation regimes including well-watered, mild and severe water deficit stress. Drought stress decreased the relative chlorophyll content (RCC), the relative water content (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Results revealed that EOC was affected by water deficit, in accordance with Bettaieb et al [12] in Salvia officinalis and Alinian [10] in cumin and coriander [42]. Furthermore, water stress affected the EOC by PODF, indirectly, which is obvious from the difference between EOC and AdjEOC.…”
Section: Essential Oil Contentsupporting
confidence: 77%
“…Results revealed that EOC was affected by water deficit, in accordance with Bettaieb et al [12] in Salvia officinalis and Alinian [10] in cumin and coriander [42]. Furthermore, water stress affected the EOC by PODF, indirectly, which is obvious from the difference between EOC and AdjEOC.…”
Section: Essential Oil Contentsupporting
confidence: 77%
“…It has been previously shown that the amount and composition of substances and secondary metabolites can be affected by water deficit stress in some medicinal plants [ 24 , 25 ]. In some studies, an enhancing effect of water deficit stress on the biosynthesis of essential oils were observed [ 26 , 27 , 28 , 29 , 30 ]. Under stressful growth conditions, secondary metabolite and/or substance production in plants can be enhanced to prevent oxidization in plant cells.…”
Section: Introductionmentioning
confidence: 99%